Social Support Quality in Internet Based Information and Communication: From "Digital Divide" to "Voice Divide" - Alexandra Klein (Social Work & Society, 2004)
National and international studies demonstrate that the number of teenagers using the inter-net increases. But even though they actually do have access from different places to the in-formation and communication pool of the internet, there is evidence that the ways in which teenagers use the net - regarding the scope and frequency in which services are used as well as the preferences for different contents of these services - differ significantly in relation to socio-economic status, education, and gender. The results of the regarding empirical studies may be summarised as such: teenager with low (formal ) education especially use internet services embracing 'entertainment, play and fun' while higher educated teenagers (also) prefer intellectually more demanding and particularly services supplying a greater variety of communicative and informative activities. More generally, pedagogical and sociological studies investigating "digital divide" in a dif-ferentiated and sophisticated way - i.e. not only in terms of differences between those who do have access to the Internet and those who do not - suggest that the internet is no space beyond 'social reality' (e.g. DiMaggio & Hargittai 2001, 2003; Vogelgesang, 2002; Welling, 2003). Different modes of utilisation, that structure the internet as a social space are primarily a specific contextualisation of the latter - and thus, the opportunities and constraints in virtual world of the internet are not less than those in the 'real world' related to unequal distribu-tions of material, social and cultural resources as well as social embeddings of the actors involved. This fact of inequality is also true regarding the outcomes of using the internet. Empirical and theoretical results concerning forms and processes of networking and commu-nity building - i.e. sociability in the internet, as well as the social embeddings of the users which are mediated through the internet - suggest that net based communication and infor-mation processes may entail the resource 'social support'. Thus, with reference to social work and the task of compensating the reproduction of social disadvantages - whether they are medial or not - the ways in which teenagers get access to and utilize net based social sup-port are to be analysed.